Processes and Responses in Monetary Control - Bach, G. L. (The Review of Economics and Statistics, 1963)
W l THAT have we learned from ComIV Vmission on Money and Credit about processes and responses in monetary policy? So far as I can see, from Report itself, very little but perhaps experts in monetary economics were not a significant part of audience at whom Report was aimed. So most fruitful course may be to turn primarily to staff papers. Here there is substantial evidence of quantity theory reborn at least in sense that money matters a good deal in determining aggregate spending on current output and of an important postwar change in monetary theory. As noted in my introduction to this volume, this postwar shift in theory is centered in approach to demand for money and other assets. In this theory, channels through which variations in money supply affect levels of income and employment include not only a change in the interest but also changes in relative prices of all assets-real and financialwhich in turn lead to shifts in spending on existing assets and currently produced goods and services. Thus in its extreme form approach suggests that we need to look not at one interest rate but at an extremely large number, including implied interest rates on all real assets and including consumer goods of any degree of durability. In logical terms, this approach offers an elegant rapprochement for devotees of and quantity-theory approaches to role of money, and for monetary-versus-fiscal policy disputes since I930's. If look prevails, we may look back at much of this controversy as a good deal less significant than it has seemed en route. The great controversy over Is savings really equal to investment? of late I930's and early I940's springs to mind. But agreement on this mechanism doesn't necessarily tell us how important money is quantitatively. If we look at staff papers (or at least, at sample I managed), what does professional support for renaissance of money and monetary policy amount to? Friedman and Meiselman, as might be expected, plump for money as a prime determinant of level of spending on current output, and show convincingly that a simple, traditional monetary model versus a simple traditional Keynesian model test gives verdict clearly to stability for velocity over stability for ratio of autonomous to income, including cases where reasonable lags are introduced. Moreover, they go on to spell out portfolio balancing mechanism as at least a plausible mechanism through which this monetary effect may be exerted. If we take Section VI of their paper as a statement of new monetary orthodoxy, on intellectual grounds at least a good deal of basis for long quarrel between monetary and Keynesian economists has been reasoned (or compromised) away. Few, even most ardent neo-Keynesians, would disagree that impact of open market operations may be through spreading net which Friedman and Meiselman spell outnot merely through one (bond) interest rate alone acting on investment decisions. The major challenge to now generally accepted fiscal policy position as our really powerful stabilization tool becomes a strong one if a reasonably stable demand for money is added to mechanism as at least Friedman and Meiselman argue. The C.M.C. staff papers contain no empirical answer to Friedman and Meiselman challenge to show better results with another model. Tobin, in his paper on debt policy, provides an elegant statement of a very similar mechanism through which changes in money stock and liquidity may influence spending decisions on current output through rebalancing of asset portfolios. But I hope it will not be too dissident a note to suggest that we really know very little empirically about validity of this description of channels of monetary policy; and that elaborate portfolio-balancing general equilibrium approach lacks intuitive appeal